ANALISIS TINGKAT KEKRITISAN AIR UNTUK KEBERLANGSUNGAN USAHATANI PANGAN MENDUKUNG ADAPTASI TERHADAP PERUBAHAN IKLIM : STUDI KASUS DI PULAU SULAWESI - Woro Estiningtyas; Budi Kartiwa; Dariin Firda (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
Analysis of Water Criticality Level as a Basis for Adaptation of Climate Change for Food Sustainabilty Farming: A Case Study in Sulawesi Island. Water is a major factor for the growth and sustainability of crop production. The occurrence of climate change has a significant impact on the agricultural sector including water resources. Rainfall as the main water source will change its pattern, intensity and distribution due to climate change so that it greatly affects water availability. This paper aimed to present the level of water criticality and distribution at the district/city level on Sulawesi Island. The level of water criticality was determined based on the ratio between availability and demand for water. Discharge simulations were generated based on the GR2M model. Around 32.1% of district on Sulawesi Island were still at the